(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The purpose of this research was for molecular identification and antibiotic resistance of Escherichia coli isolated from UTI patients. More than 50 urine samples from patients with urinary tract infections were gathered from Hilla's hospitals and medical clinics. PCR was used to confirm the presence of 16srRNA, acrA, and acrB genes in the bacterial isolates, which were identified using standard methods. Out of 50 clinical samples, 23 isolates of E. coli were detected and identified using conventional techniques. From these 23 samples, 22 isolates were verified by PCR. The results of antibiotics sensitivity test showed that all isolates were MDR were higher resistant to the carbenicilline 23 (100 percent ), Erythromycin 22 (95.7 percent ), Cefotaxime 17 (73.9 percent ), Novobiocin 16 (69.5 percent ),Tetracycline 14 (60.9 percent ) ,Ciprofloxacin 12 (52.2 percent ), Gentamicin 8 (34.8 percent ) and Nitrofurantoin 1 (4.3 percent ). (4.3 percent ). All isolates of E. coli isolated from urinary tract infections showed multiple resistance for antibiotics), multidrug resistance (MDR) was the highest antibiotic resistance carbenicillin with a percentage of (100%) and less resistance to the antibiotic nitrofurantoin with a percentage of (4.3%).